An evaluation of biomotor characterstics according to biological maturation level in 11-12 age soccer players - Aydin, Serkan (2023)
The aim of this study was to evaluate the biomotor characteristics of 11–12-year-old soccer players according to their biological maturation level. The participants in the study were divided into 3 groups according to their peak height (PHV) values which determine their biological maturation levels. The mean age, height and body mass of the participants were 11.22±0.42 years, 163.56±9.30 cm, 54.37±10.05 kg for the PHV1 group, 11.46±0.55 years, 152.45±5.22 cm, 41.32±4.84 kg for the PHV2 group, 11.10±0.31 years, 148.60±4.42 cm, 39.21±4.59 kg for the PHV3 group. The participants were competitive athletes with at least 2 years of continuous training and competition experience. The maturation level of the participants, was determined by Mirwald equation. Biomotor characteristics of the participants were determined by hand grip strength and back leg strength, standing long jump, flexibility, yo-yo intermittent recovery tests. Data were analyzed using IBM SPSS 26 package program. One-way analysis of variance (ANOVA) was used for comparison between groups and Tukey HSD test was used for Post Hoc comparisons of significant relationships. As a result of the evaluation made according to the biological maturation levels of the participants, numerically positive effects on biomotor characteristics were found as the biological maturation level increased. A statistically significant difference between the data constituting the positive effects was observed only in the hand grip strength data. According to the Tukey multiple comparison analysis, it was determined that this significant difference occurred as the biological maturation level increased. As a result of the data obtained as a result of our research, it was concluded that the biomotor characteristics of 11-12 age group soccer players developed positively according to the level of biological maturation. In line with these results, it can be stated that biological maturation has a positive effect on biomotor characteristics.